THE RELATIONSHIP BETWEEN FOREIGN LANGUAGE ANXIETY AND SELF-CONFIDENCE OF 11th GRADE STUDENTS IN LEARNING ENGLISH AT SMKS 1 TAMANSISWA PEMATANGSIANTAR - Nita Utami Sinurat; Bernieke Anggita Ristia Damanik; Rudiarman Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to investigates the relationship between foreign language anxiety and self-confidence among 11th grade students learning English at SMKS 1 Tamansiswa Pematangsiantar, a vocational high school in Indonesia. Foreign language anxiety (FLA), encompassing communication apprehension, test anxiety and fear of negative evaluation, is known tu hinder language acquisition, while self-confidence suppoots persistence and willingness to communicate in the target language. Using Horwitz et al’s Foreign LanguageClassroom Anxiety Scale (FLCAS) and Park and Lee’s Self-Confidence Questionnaire, data were collected from 45 eleventh grade students during the 2025/2026 academic year. The results reveal a strong and significant negative correlation ( r = -0.880, p < 0.001) between foreign language anxiety and self-confidence. Most sudents experienced moderate to high anxiety and low self-confidence, which negatively impacted their English learning outcomes. The findings support the affective filter hypothesis, indicating that anxiety reduces self-confidence and limits language engagement. Recommendations focus on anxiety reduction and confidence building interventions in the classroom such as supportive teaching methods, collaborative activities and positove feedback to enhance students’ English proficiency and future career readiness.